2015
DOI: 10.1016/j.mod.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Following the intracellular localization of the iab-8ncRNA of the bithorax complex using the MS2-MCP-GFP system

Abstract: Homeotic genes are aligned on the chromosome in the order of the segments that they specify along the antero-posterior axis of the fly. In general the genes affecting the more posterior segments repress the more anterior genes, a phenomenon known as "posterior dominance". There is however a noticeable exception to this rule in the central nervous system of Drosophila melanogaster where the posterior Abd-B gene does not repress the immediately more anterior abd-A gene. Instead, abd-A repression is accomplished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…If convergent orientation at contact sites were energetically preferred, it would overcome any of the relatively small costs of bending the large chromatin region within the loop and there would be no requirement that sites be oriented on the DNA sequence (but see the comment in legend of Fig. 5, below;Arib et al 2015) It is apparent that these domains are formed by a nonequilibrium process, and some recent studies indicate what form it might take. In a review of Guo and colleagues (Rao et al 2014;Guo et al 2015), Nichols and Corces (2015) suggested that the ability of CTCF to bend DNA at one end of its binding site (Arnold et al 1996; MacPherson and Sadowski 2010) would create an incipient loop, which could then enlarge until a mating CTCF was encountered.…”
Section: Mechanisms For Generating Convergencementioning
confidence: 99%
“…If convergent orientation at contact sites were energetically preferred, it would overcome any of the relatively small costs of bending the large chromatin region within the loop and there would be no requirement that sites be oriented on the DNA sequence (but see the comment in legend of Fig. 5, below;Arib et al 2015) It is apparent that these domains are formed by a nonequilibrium process, and some recent studies indicate what form it might take. In a review of Guo and colleagues (Rao et al 2014;Guo et al 2015), Nichols and Corces (2015) suggested that the ability of CTCF to bend DNA at one end of its binding site (Arnold et al 1996; MacPherson and Sadowski 2010) would create an incipient loop, which could then enlarge until a mating CTCF was encountered.…”
Section: Mechanisms For Generating Convergencementioning
confidence: 99%
“…The effects of mutations in such genes can be probed to understand the nature of variability present in the system. The other possibility pertaining to the differential dosages of ncRNAs can be probed by in-situ hybridization (Arib et al 2015). However, the de nitive changes in the ncRNAs corresponding with the adult phenotypes require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently adapted this system for transgenic use in Drosophila in order to visualize nanos (nos) mRNA during oogenesis, and showed that localization occurred by diffusion/entrapment [26]. It has since been used by us and others to investigate trafficking of a variety of mRNAs in oocytes, embryos, and neurons [19, 2731] (Figures 3, 4) and a recent study has illustrated its utility for investigating localization of long non-coding RNAs [32]. The transgenic MS2/MCP system has also been used in Drosophila embryos to monitor native transcripts and transcriptional dynamics in individual nuclei cells and to track transcriptional activity within groups of cells [33, 34].…”
Section: In Vivo Fluorescent Labeling Of Mrnamentioning
confidence: 99%